2009
DOI: 10.1021/ie800941x
|View full text |Cite
|
Sign up to set email alerts
|

Fluidized-Bed Coating with Sodium Sulfate and PVA−TiO2, 2. Influence of Coating Solution Viscosity, Stickiness, pH, and Droplet Diameter on Agglomeration

Abstract: In the first part of this study [Hede, P. D.; Jensen, A. D. Ind. Eng. Chem. Res. 2009, 49, 1914, agglomeration regime maps were developed for two types of coatings: sodium sulfate and PVA-TiO 2 . It was observed here how the agglomeration tendency is always lower for the salt coating process than for the polymer coating process, under similar process conditions. This is investigated further in this second part and concluded to be due to differences in coating solution stickiness, rather than differences in bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…These results indicate that the colloidal silica particles were being stabilized as agglomerates and could not adequately be dispersed through the polymer layer, which resulted in a coating layer more comparable to when S1 was used (when no colloidal silica was present) than S2 or S5 where the colloidal silica particles were dispersed effectively. These results are comparable to the findings of Hede et al who observed that improved TiO 2 dispersion in a PVA solution decreased the "stickiness" of the suspension, and in turn reduced agglomeration of 400 -500 m sodium sulfate beads [52].…”
Section: The Effect Of the Presence Of Colloidal Silica And Colloid supporting
confidence: 90%
See 1 more Smart Citation
“…These results indicate that the colloidal silica particles were being stabilized as agglomerates and could not adequately be dispersed through the polymer layer, which resulted in a coating layer more comparable to when S1 was used (when no colloidal silica was present) than S2 or S5 where the colloidal silica particles were dispersed effectively. These results are comparable to the findings of Hede et al who observed that improved TiO 2 dispersion in a PVA solution decreased the "stickiness" of the suspension, and in turn reduced agglomeration of 400 -500 m sodium sulfate beads [52].…”
Section: The Effect Of the Presence Of Colloidal Silica And Colloid supporting
confidence: 90%
“…The colloidal silica particles encased in the film coating will introduce asperities to the polymer coated ibuprofen to reduce cohesion, create separation between the core particles, and ultimately prevent agglomeration during spray coating. Several other authors have shown that agglomeration can be minimized when colloidal dispersions are sprayed instead of polymeric solutions [51,52]. Figure shows that the presence of the 180 nm colloidal silica particles allowed for higher coating weight gains without significant agglomeration.…”
Section: The Effect Of the Presence Of Colloidal Silica And Colloid mentioning
confidence: 89%
“…The conclusions from the experiments in the first part of this study and the second part of this study, especially regarding the viscosity and stickiness, may be used to suggest a modification to the original viscous Stokes number. Instead of defining St v based on the viscous energy dissipated in the liquid bridge, the suggestion is to define a tack Stokes number ( St tack ) based on the tack work measured in the probe tack test.…”
Section: Testing Possible Causes For Differences In Processingmentioning
confidence: 97%
“…Analogously, an increased liquid layer (increasing h liq values) result in larger St v * values meaning that more particles will agglomerate. More information on the viscous Stokes theory may be found in the work of Ennis et al, Tardos and co-workers, , and Salman et al…”
Section: Viscous Stokes Theory: Agglomeration Of Nondeformable Granulesmentioning
confidence: 99%
“…The surface waves were taking time to grow and destabilize the liquid sheet. 34 In response, the sheet surface was not thin enough to initiate the breakup at near nozzle points.…”
Section: Axial Smd Distributionmentioning
confidence: 99%